Effect of using a wearable device on clinical decision-making and motor symptoms in patients with Parkinson's disease starting transdermal rotigotine patch: A pilot study. (July 2019) - Isaacson, Stuart H.; Boroojerdi, Babak; Waln, Olga; McGraw, Martha; Kreitzman, David L.; Klos, Kevin; Revilla, Fredy J.; Heldman, Dustin; Phillips, Maureen; Terricabras, Dolors; Markowitz, Michael; Woltering, Franz; et al.
Abstract: Background: Feedback from wearable biosensors may help assess motor function in Parkinson's disease (PD) patients and titrate medication. Kinesia 360 continuously monitors motor symptoms via wrist and ankle sensors. Methods: PD0049 was a 12-week pilot study to investigate whether using Kinesia 360 at home could improve motor symptom management in PD patients starting transdermal dopamine agonist rotigotine. Adults with PD and insufficiently controlled motor symptoms (prescribed rotigotine) were randomized 1:1 to Control Group (CG) or Experimental Group (EG) before starting rotigotine. Motor symptoms were assessed in all patients at baseline and Week 12 (W12) using Unified PD Rating Scale (UPDRS) III and Kinesia ONE, which measures standardized motor tasks via a sensor on the index finger. Between baseline and W12, EG used Kinesia 360 at home; clinicians used the data to supplement standard care in adjusting rotigotine dosage. Results: At W12, least squares mean improvements in UPDRS II (−2.1 vs 0.5, p  = 0.004) and UPDRS III (−5.3 vs −1.0, p  = 0.134) were clinically meaningfully greater, and mean rotigotine dosage higher (4.8 vs 3.9 mg/24 h) in EG (n = 19) vs CG (n = 20). Mean rotigotine dosage increase (+2.8 vs + 1.9 mg/24 h) and mean number of dosage changes (2.8 vs 1.8) during the study were higher in EG vs CG. Tolerability and retention rates were similar. Conclusion: Continuous, objective, motor symptom monitoring using a wearable biosensor as an adjunct to standard care may enhance clinical decision-making, and may improve outcomes in PD patients starting rotigotine. Highlights: We compared Kinesia 360 and standard care alone in PD patients starting rotigotine. Kinesia 360 group had greater motor symptom improvement than standard care group. Kinesia 360 group had more rotigotine dosage adjustments during the 12-week study. Mean rotigotine dosage was higher in the Kinesia 360 group at the end of the study. Wearable sensors may improve clinical decision-making and outcomes in such patients.